Properties of Cu2ZnSnS4 Films by Sulfurization of CuS-SnS-ZnS Precursors Using Ditert-butylsulfide at Atmospheric Pressure. (1st January 2015) - Ni, Ho-Ching; Lin, Chu-Hsien; Lo, Ko-Ying; Tsai, Cheng-Hsiu; Chen, Tzu-Pei; Tsai, Jai-Lin; Gong, Jyh-Rong
Abstract : Cu2 ZnSnS4 (CZTS) films were prepared by sulfurization of chemical bath deposited (CBD) CuS-ZnS-SnS precursors at atmospheric pressure using ditert-butylsulfide (DTBS). The characteristics of DTBS-sulfurized CZTS films were investigated by X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), absorption spectroscopy, and X-ray photoelectron spectroscopy (XPS). Based on the XRD and Raman results, tin sulfide (SnS) was formed at 500 and 550°C under an insufficient exposure of sulfur-containing ambient. An increment of sulfurization time interval or DTBS admittance at high sulfurization temperatures tended to enable the formation of CZTS structure with improved stoichiometry and optical quality. Atmospheric pressure sulfurization of CZTS using DTBS was found to constitute another viable choice for the sulfurization of CuS-ZnS-SnS precursor. Under sufficient replenishment of DTBS at elevated sulfurization temperature, CZTS with improved stoichiometry was achieved by using DBTS sulfurization at atmospheric pressure.